2022
DOI: 10.1186/s13073-022-01018-w
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation reveals distinct cells of origin for pancreatic neuroendocrine carcinomas and pancreatic neuroendocrine tumors

Abstract: Background Pancreatic neuroendocrine neoplasms (PanNENs) fall into two subclasses: the well-differentiated, low- to high-grade pancreatic neuroendocrine tumors (PanNETs), and the poorly-differentiated, high-grade pancreatic neuroendocrine carcinomas (PanNECs). While recent studies suggest an endocrine descent of PanNETs, the origin of PanNECs remains unknown. Methods We performed DNA methylation analysis for 57 PanNEN samples and found that distinc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…The PNET methylome has been profiled, in 24 studies in a gene specific manner (Dammann et al, 2003, House et al, 2003, Arnold et al, 2007, Malpeli et al, 2011, Muscarella et al, 1998, Serrano et al, 2000, Bartsch et al, 2000, Campana et al, 2018, Chan et al, 2003, Liu et al, 2005, Ohki et al, 2014, Schmitt et al, 2014, Ushiku et al, 2016, Wild et al, 2003, Ban et al, 2022, Conemans et al, 2018, Stefanoli et al, 2014, Liu et al, 2014, Cros et al, 2016, Dejeux et al, 2009, Choi et al, 2007, Zhang et al, 2020, Evans et al, 2022a, Stricker et al, 2012 and subsequently by both global methylation (Marinoni et al, 2017) and hydroxymethylation (Sharma et al, 2022), and by specific CpG site assessment with array-based technologies. (Chan et al, 2003, Boons et al, 2020, Di Domenico et al, 2020, Lakis et al, 2021, Tirosh et al, 2019, Simon et al, 2022, Yachida et al, 2022 Out of the 24 studies looking at a specific subset of genes, 58% (14/24) have used methylationspecific polymerase chain reaction (MSP) to investigate the percentage of methylation present at specific gene promoters. However, the criteria used to classify whether a gene is methylated were not defined in most studies.…”
Section: Dna Methylation In Pnetsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PNET methylome has been profiled, in 24 studies in a gene specific manner (Dammann et al, 2003, House et al, 2003, Arnold et al, 2007, Malpeli et al, 2011, Muscarella et al, 1998, Serrano et al, 2000, Bartsch et al, 2000, Campana et al, 2018, Chan et al, 2003, Liu et al, 2005, Ohki et al, 2014, Schmitt et al, 2014, Ushiku et al, 2016, Wild et al, 2003, Ban et al, 2022, Conemans et al, 2018, Stefanoli et al, 2014, Liu et al, 2014, Cros et al, 2016, Dejeux et al, 2009, Choi et al, 2007, Zhang et al, 2020, Evans et al, 2022a, Stricker et al, 2012 and subsequently by both global methylation (Marinoni et al, 2017) and hydroxymethylation (Sharma et al, 2022), and by specific CpG site assessment with array-based technologies. (Chan et al, 2003, Boons et al, 2020, Di Domenico et al, 2020, Lakis et al, 2021, Tirosh et al, 2019, Simon et al, 2022, Yachida et al, 2022 Out of the 24 studies looking at a specific subset of genes, 58% (14/24) have used methylationspecific polymerase chain reaction (MSP) to investigate the percentage of methylation present at specific gene promoters. However, the criteria used to classify whether a gene is methylated were not defined in most studies.…”
Section: Dna Methylation In Pnetsmentioning
confidence: 99%
“…(Di Domenico et al, 2020, Boons et al, 2020, Lakis et al, 2021, Chan et al, 2018, Yachida et al, 2022 Two studies which stratified PNETs from PNECs, reported that PNECs have a similar methylation profile to exocrine pancreatic tissue. (Simon et al, 2022, Yachida et al, 2022 One of these studies used multiomic data to further stratify PNECs into 'ductal' (Retinoblastoma-Associated Protein (RB1) protein loss, Tumour Protein 53 (TP53) mutations and a CpG Island Methylator Phenotype (CIMP) phenotype) and 'acinar' (CDKN2A alterations, deletions or promoter hypermethylation and WNT signalling alterations) subtypes. (Yachida et al, 2022) These studies provide further evidence that PNECs are a distinct biological entity when compared to PNETs, and highlight the importance of accurate tumour diagnosis to ensure that patients receive the appropriate therapies.…”
Section: Dna Methylation To Define and Stratify Pnetsmentioning
confidence: 99%
“…performed in-depth genomic analysis of 57 pNENs (43 pNET, 14 pNEC) using DNA sequencing to identify recurrent genetic mutations. From this analysis, the authors identified two groups: Group A included mutations that are often associated with pNETs including MEN1 , DAXX , ATRX , VHL , PTEN and TSC2 , while Group B contained no mutations in DAXX , ATRX or MEN1 but contained KRAS , SMAD4 and TP53 mutations ( 39 ). Allen, et al.…”
Section: Genetic Basis Of Gep-nensmentioning
confidence: 99%
“…The Simon et al. study performed DNA methylation profiling of the 57 pNENs (43 pNET, 14 pNEC) and was able to delineate pNET tumors from NEC based on t-distributed stochastic neighbor embedding (tSNE) analysis of methylation profiles ( 39 ).…”
Section: Dna Methylationmentioning
confidence: 99%
“…A recent study performed by Simon et al [ 58 ] outlined the importance of finding molecular groups by performing genetic and epigenetic profiling of 57 PanNENs. The molecular classification accurately differentiates PanNECs that may have an exocrine cell-of-origin, from PanNETs’ endocrine cell-of-origin.…”
Section: Pathology and Molecular Subtypesmentioning
confidence: 99%